2017
DOI: 10.3390/ijms18071556
|View full text |Cite|
|
Sign up to set email alerts
|

Secreted Protein Acidic and Rich in Cysteine (SPARC) Enhances Cell Proliferation, Migration, and Epithelial Mesenchymal Transition, and SPARC Expression is Associated with Tumor Grade in Head and Neck Cancer

Abstract: Secreted protein acidic and rich in cysteine (SPARC) is a secreted protein which is involved in various biological processes. SPARC expression is associated with tumor metastasis and poor prognosis in several types of cancer. However, the SPARC-induced signaling pathway was not fully understood in head and neck cancer. In this study, our results showed that SPARC treatment promoted cell proliferation and migration in head and neck cancer cell lines FaDu and Detroit 562. In addition, SPARC induced expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
(45 reference statements)
2
29
0
Order By: Relevance
“…Our data showed that SPARC overexpression induced an EMT phenotype in A549 and H1299 cells, while knockdown of SPARC in A549 cells shown a contrary result. The positive relationship between SPARC and EMT was illustrated in melanoma cells and head and neck cancer . Previous studies have shown that SPARC regulates the interplay between myeloid‐derived suppressor cells and extracellular matrix to induce the induction of EMT in tumor cells .…”
Section: Discussionmentioning
confidence: 93%
“…Our data showed that SPARC overexpression induced an EMT phenotype in A549 and H1299 cells, while knockdown of SPARC in A549 cells shown a contrary result. The positive relationship between SPARC and EMT was illustrated in melanoma cells and head and neck cancer . Previous studies have shown that SPARC regulates the interplay between myeloid‐derived suppressor cells and extracellular matrix to induce the induction of EMT in tumor cells .…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with this result, we found that HOXC6 is a master regulator of many genes, which have documented pro-tumorigenic functions. In our studies, we identified several genes, including CEACAM6, SPARC, WNT6, CST1, MMP2, and KRT13, which have been extensively studied and demonstrated to be involved in the regulation of tumor growth, migration and invasion, cell cycle, and apoptosis (Chang et al 2018;Choi et al 2009;Dai et al 2017;Kuo et al 2014;Rizeq et al 2018;Wang et al 2018;Yusuf et al 2014;. In other types of cancers, HOXC6 has also been shown to have the capacity to regulate these cancerrelated genes.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 87%
“…More importantly, SPARC silencing significantly mitigated the VEGF-stimulated Collagen-I and MMP9 expression in HTFs and attenuated the VEGF-stimulated proliferation and wound healing of HTFs. Previous studies have shown that SPARC can modulate MMP activity in U87MG glioma cells 17 and altered MMP activity can affect the ECM remodeling and fibroblast proliferation and migration 18-19. Moreover,SPARC can promote cell adhesion 20 and SPARC deficiency inhibits cell migration in various types of cells [21][22] . It is possible that SPARC modulates MMP activity and wound healing,contributing to the progression of fibrosis 23 .…”
Section: Discussionmentioning
confidence: 99%